Pengenalan Perilaku Hidup Bersih Dan Sehat (PHBS) Melalui Permainan Play Dough Pada Anak Usia Dini Di Desa Jenggolo II, Banyuurip, Pati - Pasiningsih (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2022)
Learning from home during the COVID-19 has limited children’s opportunities to learn, including to learn about Clean and Healthy Behavior. This condition worsened by the fact that some parents need to work and have lack of education so they cannot assist their children in learning, such as the circumstances in Jenggolo II Village, Banyuurip, Pati. Thus, training is needed to introduce children to Clean and Healthy Behavior in the form of hand washing with soap. One of them is through community service activities by providing training related to the introduction of Clean and Healthy Behavior to children who live in Jenggolo II Village, Banyuurip, Pati. The training activities began with making play dough with children, watching the 6 Steps to Wash Hands’ video, and practicing hand washing with soap. The training activities went well. Children and parents gave a positive response regarding the training activities. However, further training is needed so it become a child's habit. Training activities also need to consider the characteristics of early childhood, namely learning through play.